Design And Performance Evaluation Of Solar PV System In Malaysia - Tan, Pi Hua (2016)
The technical design and performance evaluation of solar PV system are gaining increasing attention nowadays. This is to maximize the economic benefits and to shorten the investment payment period, particularly under the Feed-in Tariff incentive scheme. In light of this, this thesis presents a comparison between the performance of Thin Film (tandem junction- micro-amorphous), Heterojunction with Intrinsic Thin layer (HIT) and Mono-Crystalline (Mono) photovoltaic (PV) module technologies between estimated and real measurement data for the grid-connected PV system installed at the Research Laboratory of PV System and Smart Grid, UTeM. The respective system performances were analysed in terms of total energy yield. In addition, the rooftop and ground mounted PV system installation conditions were also considered in the study. The respective system performances were compared in terms of total energy generated, specific yield and Levelized Cost of Energy (LCOE) for PV grid parity analysis in Malaysia. The FiT degradation rate of solar PV system has been taken into consideration. The key findings suggest that under the Malaysian climate environment, the Thin Film PV system has the highest energy yield, which is mainly driven by its lower module temperature losses and minimum module fluctuation response. Moreover, under the current Feed-in Tariff scheme in Malaysia, the rooftop thin-film PV system installation has the highest economic benefit for the utility scale PV power plant. Apart from the PV system performance evaluation, the installation of an external lightning protection system is crucial for power plants to minimize PV system damages.This is because Malaysia is also one of the countries withthe highest occurrences of lightning activities in the world. Thus, it is essential for PV power plants to have adequate protection from damage and power generation losses. In this regard, two different lightning systems were considered to two different PV technology Power Plant systems. The respective system performances were compared in terms of total energy yield. The key findings suggest that the air termination lightning pole is suitable for a solar power plant particularly a Thin Film or Crystalline PV power plant system that will result in lower losses compared to the Early Streamer Emitter lightning pole for the PV Power Plant system.